2013
DOI: 10.1186/1752-153x-7-54
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a constructed wetland in Grand Marais, Manitoba, Canada: Removal of nutrients, pharmaceuticals, and antibiotic resistance genes from municipal wastewater

Abstract: BackgroundThe discharge of complex mixtures of nutrients, organic micropollutants, and antibiotic resistance genes from treated municipal wastewater into freshwater systems are global concerns for human health and aquatic organisms. Antibiotic resistance genes (ARGs) are genes that have the ability to impart resistance to antibiotics and reduce the efficacy of antibiotics in the systems in which they are found. In the rural community of Grand Marais, Manitoba, Canada, wastewater is treated passively in a sewag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 56 publications
2
28
0
1
Order By: Relevance
“…The o-DGT deployed in the wastewater treatment facility show analyte storage after exposure to a real environmental matrix and represent actual use of many passive sampling devices [9,10]. The storage data in this case were limited to the occurrence and detection of analytes at the specific sampling site, namely, atrazine, carbamazepine, gemfibrozil, naproxen, sulfamethoxazole, sulfapyridine, and trimethoprim (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The o-DGT deployed in the wastewater treatment facility show analyte storage after exposure to a real environmental matrix and represent actual use of many passive sampling devices [9,10]. The storage data in this case were limited to the occurrence and detection of analytes at the specific sampling site, namely, atrazine, carbamazepine, gemfibrozil, naproxen, sulfamethoxazole, sulfapyridine, and trimethoprim (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed stable storage with POCIS in the freezer (-20 8C) for a suite of target analytes over approximately 1.5 yr [7]. The utility of this work is evident in studies requiring storage of POCIS before analysis [9,10]. There have been studies on the stability of pharmaceutical and pesticide residues in surface waters stored refrigerated [11] and frozen in raw wastewater samples [12] and in preserved or pretreated (e.g., addition of ethylenediaminetetraacetic acid) water samples [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, similar results showing slight or no removal were obtained for CBZ and 5 of its metabolites (10,11-dihydro-10,11-dihydroxy-CBZ, 10,11-dihydro-10-hydroxy-CBZ, 10,11-epoxy-10,11-dihydro-CBZ, 2-hydroxy-CBZ and 3-hydroxy-CBZ) in German and Portuguese full-scale WWTPs (Bahlmann et al, 2014). On the other hand, full-scale constructed wetlands (CW) were useful for CBZ and SMX removal purposes (Gross, Montgomery-Brown, Naumann, & Reinhard, 2004;Matamoros, Garc ıa, & Bayona, 2008;Hijosa-Valsero, Matamoros, Mart ın-Villacorta, B ecares, & Bayona, 2010;Anderson et al, 2013;Lee, Lee, Park, Kim, & Cho, 2013). Nevertheless, conflicting results have been reported by these authors, ranging from no effective removal of both compounds in a study conducted in Canada (Anderson et al, 2013), from 15 to 37% CBZ removal efficiencies in full-scale and surface flow CW reported in Spain (Hijosa-Valsero et al, 2010).…”
Section: Full-scale Wwtpsmentioning
confidence: 99%
“…Environment Research, Volume 86, Number 10-Copyright © 2014 Water Environment FederationUsing a treatment facility composed of a lagoon followed by wetland as a model system the presence and ARGs in lagoon outputs, and their potential removal by the treatment wetland prior to release to surface waters in 2012 were investigated. The results of this study indicated that while the treatment wetland may effectively attenuate excess nutrients and remove some micropollutants and bacteria, it does not does not achieve efficient ARGs removal(Anderson et al, 2013).Burch et al (2013) investigated whether airdrying beds reduce antibiotic resistance gene (ARC) concentrations in residual municipal wastewater solids. Three laboratory-scale drying beds were operated for a period of nearly 100 days.…”
mentioning
confidence: 97%